Measure and evaluate the return and risk formulas of Islamic Finance: Empirical study of the state of Jordan Islamic Bank and Islamic Arab International Bank - المشهداني عبد الرحمن حمود (Journal of Economics and Administrative Sciences, 2013)
The study aims to measure and evaluate the return and the risk formulas of Islamic finance of Jordan during the period (2000 – 2009) according of increasing importance of these banks in recent and coming years to face challenges to maximize returns and minimize risks through financing with Islamic formula to investigate of existence statistical significant relationship between returns and risking Islamic bank , has been use of financial other statistical measurement. Measuring return and risk of Islamic banks have not been widely considered ,except in few descriptive studies . The controversy among academic and professionals about hot to measure and evaluate a comprehensive performance of Islamic banks is a continuous phenomenon . This is the core problem of this research , which has its proposed solution related with the hypothesis that “ there is a significant relationship between risk and return of Islamic financing , which in turn will effects its valuation measures”. The study proved the existence of some positive weak and insignificant relation between return and risk of bank that the study taking another some of negative weak relation, the result didn’t appear large statistical significant relation between return and risk of banks that financing with different Islamic formula. Many recommendations have thrown , the most important one is the necessity of developing new measures for managing risks of Islamic banks instead of the traditional ones.